THE ROLE OF PRE-TRANSPLANT AND DE NOVO ALLOANTIBODIES IN KIDNEY TRANSPLANTATION - A. I. Sushkov; V. Y. Abramov; Y. G. Moysyuk (Вестник трансплантологии и искусственных органов, 2011)
Kidney transplant recipients may have pre-transplant alloantibodies or develop de novo anti-HLA and non- HLA antibodies after transplantation. Although these antibodies may be donor-specific or non-donor-specific, their presence may increase the risk for acute and chronic rejection, thereby decreasing allograft survival. The introduction of high sensitive and specific methods to detect anti-HLA antibodies, both before and after trans- plantation, will help to define transplant recipients who might be at increased risk for early or late allograft failure. Moreover, knowledge of alloantibody status before transplantation may help to guide the appropriate use of immunomodulatory agents and plasmapheresis to remove anti-HLA antibodies or downregulate their production. The review focuses on the associations between renal graft outcome and pre-transplant and de novo alloantibodies.